Tinagma asignatum Gaedike & Falck, sp. n. from the Canary Islands (Spain) (Lepidoptera: Douglasiidae) - R. Gaedike; F. Falck (SHILAP)
Tinagma asignatum Gaedike & Falck, sp. n. is described from the Canary Island, Gran Canaria. Images of the adult and the genitalia are presented.